The Role of Social Media Marketing Activities in Building Local Product Brand Love of Aerostreet Shoes in Indonesia - Atmaja, Firza Isna Yudha; Nurhadi, Mochamad; Lindiawati, Lindiawati; Marta, Laila Saleh (Universitas muhammadiyah palembang, 2023)
Social media marketing activities (SMMA) in Indonesia after the Covid-19 pandemic have become one of the main tools in supporting the growth of SME products sales. This research is aimed at analyzing the role of social media marketing activities in building brand love for local shoes in Indonesia named Aerostreet mediated by brand consciousness, brand trust, and brand loyalty. Using purposive sampling method succeeds to collect 235 data. The data was analyzed using structural equation modeling supported by partial least squares. The research results show that SMMA do not play a direct role in building brand love, but through the full mediation of brand consciousness, brand trust, and brand loyalty instead. The research result also shows positive influence of SMMA on brand consciousness and brand trust as well as the positive influence of brand consciousness and brand trust on brand loyalty. Looking at theses result especially the point that SMMA does not significantly influence the brand love, but brand loyalty does, so the company should encourage the SMMA quality to make customers have strong brand consciousness, and later on this can lead to achieve strong brand loyalty which is in turn can influence the brand love of customers to Aerostreet shoes.